Pembuatan Biodiesel Dari Minyak Kapuk Menggunakan Katalis Lempung : Studi Regenerasi Katalis Dalam Proses Produksi - Genardus Oktavri Sijabat; Syaiful Bahri; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Petroleum oil still serves as a primary source of energy and national fuel. Oil reserves in Indonesia are depleting so substitution of fuel that derived from petroleum have to be sought. Recent years, a lot of research has done, whose purpose to find a fuel that can be an alternative source one of that is biodiesel. Raw material for making biodiesel can be from animal fat or vegetable oil. One type of vegetable oil that can be used as a raw material source of energy is kapok wood. This research is aimed to make biodiesel from cotton oil, to study factors which influences production, such as acid-based activated catalyst, the regeneration catalyst, and to determine the physical and chemical properties of biodiesel. The transesterification process was done on a mole ratio of oil: methanol 1: 9, oil mass 50 grams, the weight of the catalyst 1%-wt, temperature of 60°C during 90 minutes, the activation of clay catalysts are in acids and bases, and then recycle and regeneration of catalyst. This study given the biodiesel result having the largest yield of alkaline activation of the catalyst as much as 93.1%. Characterization of physical properties of biodiesel have a density 871 kg/m3, kinematic viscosity 3.5 mm2/s, acid number 0.37 mg KOH/g sample, and the flash point 210oC respectively. The catalyst regeneration cannot restore 100% reactivity of catalyst.Keywords: biodiesel, clay, recycle, regeneration, transesterification